Assessment of service quality: an exploratory study at bars in São Paulo - Luzzi Las Casas, Alexandre; Claudia Suszek, Ana (Revista Gestão da Produção Operações e Sistemas, 2009)
The objective of this study is to analyze an empirical application of the assessment instrument based on the moments of truth concept and verify its weaknesses and strengths as applied to the measurement of quality service for business enterprises. The assessment focus is related to all points of customer interaction within an organization that cause an impression. The exploratory research was conducted in three steps: first, it evaluated and checked forms and procedures; second, the assessment instrument as well as field procedures were adjusted, applying them to a larger number of mysterious shoppers. Finally, a new survey was conducted on the same study subjects. We conclude that the instrument satisfies assessment criteria for both: the clients and mysterious shoppers, proving to be a proper tool to improve service quality. However, due to certain limitations such as the subjectivity of respondents and researchers, it demands care in its use.